2021
DOI: 10.3390/e23101342
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Reflecting Surface Assisted Multi-User Robust Secret Key Generation for Low-Entropy Environments

Abstract: Channel secret key generation (CSKG), assisted by the new material intelligent reflecting surface (IRS), has become a new research hotspot recently. In this paper, the key extraction method in the IRS-aided low-entropy communication scenario with adjacent multi-users is investigated. Aiming at the problem of low key generation efficiency due to the high similarity of channels between users, we propose a joint user allocation and IRS reflection parameter adjustment scheme, while the reliability of information e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In [23], channel key extraction in a static multi-user down link scenario is considered. It is observed that due to the high channel similarity between users, the problem of low-key generation arises.…”
Section: Related Workmentioning
confidence: 99%
“…In [23], channel key extraction in a static multi-user down link scenario is considered. It is observed that due to the high channel similarity between users, the problem of low-key generation arises.…”
Section: Related Workmentioning
confidence: 99%
“…Considered promising technology, intelligent reflecting surfaces (IRSs) have recently received substantial attention [12][13][14][15][16]. IRS consists of a large number of passive elements which can introduce controllable phase shifts.…”
Section: Introductionmentioning
confidence: 99%
“…They present their results using two metrics which are SKR and key mismatch rate (KMR). The authors in [8] propose a joint user allocation scheme and an RIS reflection parameter adjustment scheme to enhance key generation efficiency in a multi-user communication scenario. They compare the result against a scheme without an RIS and find that the RIS indeed boosts performance by reducing channel similarities between adjacent users and thus the enhancing efficiency of key generation.…”
Section: Introductionmentioning
confidence: 99%